Comparison of Classical and Modern Interpretations in Interpreting Verses About Peace of Mind - Jamalulel, Dwi Rahmawati (Averroes: Journal for Science and Religious Studies, 2025)
Background: This study examines the Qur’anic concept of spiritual tranquility (as-sakīnah and an-nafs al-muṭma’innah) through an integrative approach that combines classical and modern exegesis with contemporary psychological theory. In the modern context of rising psychological distress, the Qur’anic paradigm of inner peace offers a holistic framework that unites theological, emotional, and cognitive dimensions. Methods: Using a qualitative hermeneutic and comparative approach, this research analyzes interpretations from classical scholars such as Ibn Kathir alongside modern exegetes including Quraish Shihab and Sayyid Qutb. The analysis also incorporates interdisciplinary insights from psychology and neuroscience to elucidate the relevance of spiritual practices in emotional regulation. Key Findings: The study reveals a paradigmatic shift from a purely theocentric understanding of tranquility to a psychospiritual model emphasizing self-regulation, faith internalization, and emotional balance. Empirical evidence, such as Rahmatullah and Syafii (2025), demonstrates that spiritual activities like dhikr enhance dopamine levels and reduce cortisol, supporting the link between spirituality and neuropsychological well-being. Contribution: The research formulates a spiritual–psychological peace model that bridges Qur’anic interpretation with modern psychological frameworks, offering theoretical and therapeutic implications for Islamic-based psychotherapy. Conclusion: Spiritual tranquility in the Qur’anic perspective is not a passive state but an active psychological process that harmonizes faith, cognition, and emotion, providing a valuable foundation for contemporary mental health discourse.